Systems analysis of barrier molecule and ARNT-related gene expression regulation in melanoma. (2nd December 2019) - Leick, Katie M.; Obeid, Joseph M.; Bekiranov, Stefan; Slingluff, Craig L.
ABSTRACT: Background : We have identified, in melanomas, a set of genes encoding proteins that mediate mechanical barrier function in normal skin (barrier molecule genes, BMGs) and whose overexpression is associated with decreased immune signatures and shorter patient survival. The most overexpressed of these, filaggrin (FLG), is expressed on chromosome 1q21.3, which also encodes genes of the epidermal differentiation complex (EDC). EDC genes may be regulated by the transcription factors (TFs) AHR and ARNT. We hypothesized that ARNT-related genes would be expressed concordantly with BMG and EDC genes, inversely associated with immune signatures, and enhanced by 1q21.3 copy gain. Methods : Gene expression data from human melanomas in the Cancer Genome Atlas (TCGA), and a validation GEO dataset were evaluated, with copy number profiles from TCGA. Expression of Th1 immune genes and BMG/EDCs at 1q21.3 was visualized using clustered copy number and mRNA profiles. Associations of clusters and 1q21.3 copy number with patient survival and mRNA expression were assessed using Kaplan Meier curves, log-rank tests, and Wilcoxon rank sum tests. Results : BMGs are concordantly expressed with EDC genes. Clustering divided tumors into 4 categories: (1) Immune HI, (2) BMG/EDC HI, (3) ARNT HI, (4) Mixed. Both ARNT HI and BMG/EDC HI tumors had low immune signatures and significantly shortened survival. KLF4 and FOXF2 are putative TFs that may regulate these genes. Conclusions : ARNT HI tumors may represent another subset of tumors, in addition to BMG/EDC HI tumors, with barriers to immune infiltrates, likely with different mechanisms. These genes have prognostic significance and may be relevant targets for future therapy.